Expression of SANT/HTH Myb mRNA, a plant morphogenesis-regulating transcription factor, changes due to viroid infection - Lomnická, Anna (Jihočeská univerzita, 2016)
Potato spindle tuber viroid (PSTVd) belongs to plant-pathogenic, circular, non-coding RNAs. Its propagation is accompanied by (mis)regulation of host genes and induction of pathogenesis symptoms including changes of leaf morphogenesis depending on the strength of viroid variant. We found strong genotype-dependent suppression of tomato morphogenesis-regulating transcription factor SANT/HTHMyb (SlMyb) due to viroid pathogenesis. Its relative mRNA level was found to be significantly decreased in PSTVd-sensitive tomato (cvs Rutgers and Heinz 1706) due to degradation processes, but increased in PSTVd-tolerant (cv. Harzfeuer). In heterologous system of Nicotiana benthamiana, we observed a SlMyb-associated necrotic effect in agroinfiltrated leaf sectors during ectopic overexpression. Leaf sector necroses were accompanied by activation of nucleolytic enzymes but were suppressed by a strongly pathogenic PSTVd variant. Contrary to that, PSTVd's effect was inhibited by the silencing suppressor p19. It was found that in both, Solanum lycopersicum leaves and N. benthamiana leaf sectors, SlMyb mRNA degradation was significantly stronger in viroid-infected tissues. Necroses induction as well as gene silencing experiments using the SANT/HTH-Myb homologues revealed involvement of this Myb in physiological changes like distortions in flower morphogenesis and growth suppression.
Expression of SANT/HTH Myb mRNA, a plant morphogenesis-regulating transcription factor, changes due to viroid infection
Keywords: mRNA target; RNA decay; biolistic plant inoculation; transgenote; Nicotiana benthamiana; Solanum lycopersicum; mRNA target; RNA decay; biolistic plant inoculation; transgenote; Nicotiana benthamiana; Solanum lycopersicum